Impact of a Segmented-Scan Strategy on Residual Stress and Fit Accuracy of Dental Prostheses Fabricated via Laser-Beam Powder-Bed Fusion - Yoshio Kobayashi; Atsushi Takaichi; Yuka Kajima; Wenrui Qu; Noriyuki Wakabayashi (Journal of Manufacturing and Materials Processing)
The laser-beam powder-bed fusion (PBF-LB) method enables the semi-automatic fabrication of complex three-dimensional structures, making it useful for dental prostheses. However, residual stress during fabrication can cause deformation. Herein, we applied the segmented-scan strategy to three-unit fixed dental prostheses (FDPs) and evaluated its effects on residual stress and fit accuracy compared to conventional methods. Three-unit FDPs consisting of two abutments and a pontic were fabricated using a PBF-LB machine with Co-Cr-Mo powder. In the segmented-scan group, pontics and abutments were scanned separately to shorten the scan vector. Fit accuracy was assessed by measuring the gap between the abutment and the FDPs. Residual stress was measured in the X and Y directions at three points using X-ray diffraction, while CT scans were used to count internal microstructures. The residual stress was lower in the X-direction in the segmented-scan group (24.61–217.17 MPa, respectively) than in the control group (187.70–293.71 MPa, respectively). However, no significant differences in fit accuracy were observed (p < 0.05). The segmented-scan strategy reduced residual stress in the X-direction but did not improve the fit accuracy. Applying this strategy to dental prosthetic devices can shorten the scan vector and reduce residual stress.